1997
DOI: 10.1055/s-2007-979490
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind Study Comparing Paroxetine and Maprotiline in Depressed Outpatients

Abstract: A double-blind multicenter randomized parallel group study comparing paroxetine and maprotiline was carried out in a total of 544 outpatients. Included were patients with varying degrees of severity of depressive symptoms who fulfilled modified RDC criteria for either Minor or Major Depression and showed a HAMD-17 score of > or = 13. No concomitant benzodiazepine treatment was allowed. Duration of treatment was 6 weeks, after an initial wash-out period. Doses were fixed during the first 3 weeks of treatment, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 5 publications
0
9
1
3
Order By: Relevance
“…The high percentages of responders observed in this study, although reported previously in other studies 10,[22][23][24] , are probably in part due to an additive placebo effect, which includes the beneficial effects of increased patient-clinician interaction. The lack of a placebo-controlled arm does not allow this effect to be quantified exactly.…”
Section: Discussioncontrasting
confidence: 50%
“…The high percentages of responders observed in this study, although reported previously in other studies 10,[22][23][24] , are probably in part due to an additive placebo effect, which includes the beneficial effects of increased patient-clinician interaction. The lack of a placebo-controlled arm does not allow this effect to be quantified exactly.…”
Section: Discussioncontrasting
confidence: 50%
“…Although not listed in DSM-IV as a diagnostic criterion for MDD, it has been estimated that as many as 85 % of adults with depression have significant symptoms of anxiety (Gorman, 1996(Gorman, /1997. In this context, it is clear that all existing antidepressants successfully ameliorate anxiety as a component of depression, including those that selectively block NE reuptake (Ferguson et al, 2002;Kleber, 1979;Nelson, 1999;Nystrom and Hallstrom, 1985;Stahl et al, 2002;Szegedi et al, 1997), as well as bupropion (Trivedi et al, 2001) and mirtazapine (Fawcett and Barkin, 1998), which has a prominent noradrenergic component to its complex pharmacology (Frazer, 1997). Later in this review, with respect to the specific behavioural dimensions that may be affected by drugs regulating noradrenergic and serotonergic function, we will discuss how it may be that SSRIs can be effective in both MDD and the various anxiety disorders, whereas selective NRIs seem to improve non-specific symptoms of anxiety, but are less effective against other symptoms, e.g.…”
Section: Commentmentioning
confidence: 99%
“…Subsequent clinical trials have compared paroxetine with tricyclic and related antidepressants, demonstrating approximate therapeutic equivalence between treatment groups (3,23,71,86,95,96,103,104). A large study, involving 717 outpatients with major depression, demonstrated reduction of baseline HDRS scores by 37.9% with paroxetine, 35.1% with imipramine, and 21.8% with placebo.…”
Section: Clinical Studies Depressionmentioning
confidence: 99%